1992
DOI: 10.1038/clpt.1992.30
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-pharmacodynamic relationships of morphine in neonates

Abstract: Morphine pharmacokinetics and pharmacodynamics (analgesia and sedation) were evaluated after continuous intravenous infusion of morphine in 19 neonates, both preterm and term, whose lungs were ventilated to relieve respiratory distress. Elimination half-life, total plasma clearance, and volume of distribution (mean +/- SD) were 9.6 +/- 3.0 hours, 2.55 +/- 1.65 ml/min/kg (area analysis) or 2.09 +/- 1.19 ml/min/kg (steady-state data), and 2.05 +/- 1.05 L/kg, respectively, and were not significantly different in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 8 publications
(10 reference statements)
5
75
2
1
Order By: Relevance
“…In a study of 10 premature neonates (26-34 weeks gestation) within the first 24 hr of life, Hartley et al (1993) found plasma concentrations in the range of 94-422 ng/ml, and similar values have been found in infants at term (Chay et al 1992). This contrasts with a study involving older children of mean age 11 years, where a mean plasma concentration of only 12 ng/ml was needed to maintain postoperative analgesia (Lynn et al 1984).…”
Section: Morphinementioning
confidence: 86%
See 2 more Smart Citations
“…In a study of 10 premature neonates (26-34 weeks gestation) within the first 24 hr of life, Hartley et al (1993) found plasma concentrations in the range of 94-422 ng/ml, and similar values have been found in infants at term (Chay et al 1992). This contrasts with a study involving older children of mean age 11 years, where a mean plasma concentration of only 12 ng/ml was needed to maintain postoperative analgesia (Lynn et al 1984).…”
Section: Morphinementioning
confidence: 86%
“…Some glucuronidation of morphine MiniReview has been found even in the very premature neonate of 24-25 weeks gestational age (Choonara et al 1989). In three studies in premature neonates of gestational age 25-36 weeks, mean clearance ranged from 2.2-2.8 ml/min./kg (Chay et al 1992;Hartley et al 1993;Mikkelsen et al 1994). In contrast, rates of morphine clearance in neonates born at term are generally greater, i.e.…”
Section: Morphinementioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it has been observed that premature infants are more tolerant of high doses of opioids than adults. For example, plasma concentrations of morphine approaching 300 ng ml-' are not associated with significant adverse effects in premature infants [3], whereas similar concentrations in the adult may cause nausea, vomiting and severe respiratory depression. The second explanation relates to the pharmacological action of buprenorphine as a partial agonist at the opioid receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown the benefit of administering morphine or diamorphine to the neonate to provide effective and safe analgesia or sedation [3,4]. In addition to pain relief, the use of a continuous infusion of an opioid in mechanically ventilated newborn infants has been shown to improve the synchronisation between the infants' own breathing and the ventilator.…”
Section: Introductionmentioning
confidence: 99%